Data supporting: 'Split anode calorimetry for plasma arc energy density measurement with laser calibration' - Chen, Guangyu; Williams, Stewart W.; Ding, Jialuo; Suder, Wojciech; Wang, Yipeng (Cranfield University, 2022)
Video shows the accelarated thermal image when the laser beam traveled acrossed the copper anodes interface.
Keywords: 'Arc profile'; 'Split anode calorimetry'; 'Plasma arc'; 'Welding'